Substantiated modelling instead of flying blind: correspondence - Brenner, Hermann; Hoffmeister, Michael; Stock, Christian (Deutsches Ärzteblatt, 2016)
Stang and co-authors present model calculations, based on the data of the US National Lung Screening Trial, of the expected effects of introducing lung cancer screening with low-dose computed tomography (CT) nationwide in Germany (1). With an...
Gesehen am 19.05.2020